First observations of confined fast ions in MAST Upgrade with an upgraded neutron camera. (7th February 2023) - Cecconello, M; Dolby, I J; Sperduti, A; Rivero-Rodriguez, J; Ericsson, G; Fitzgerald, I; Allan, S Y; Voller, J; Honey, B; Nizar, B A; Elmore, S D; ,
Abstract: Spherical tokamaks are key to the successful design of operating scenarios of future fusion reactors in the areas of divertor physics, neutral beam current drive and fast ion physics. MAST Upgrade, which has successfully concluded its first experimental campaign, was specifically designed to address the role of the radial gradient of the fast ion distribution in driving the excitation of magneto-hydrodynamic (MHD) instabilities, such as toroidal Alfvén eigenmodes, fish-bones and long-lived mode, thanks to its two tangential neutral beam injection systems, one on the equatorial plane and one that is vertically shifted 65 cm above the equatorial plane. To study the fast ion dynamics in the presence of such instabilities, as well as of sawteeth and neo-classical tearing modes, several fast ion diagnostics were upgraded and new ones added. Among them, the MAST prototype neutron camera (NC) has been upgraded to six, equatorial sight-lines. The first observations of the confined fast ion behavior with the upgraded NC in a wide range of plasma scenarios characterized by on-axis and/or off-axis heating and different MHD instabilities are presented here. The observations presented in this study confirm previous results on MAST but with a higher level of detail and highlight new physics observations unique to the MAST Upgrade. The results presented here confirm the improved performance of the NC Upgrade, which thus becomes one of the key elements, in combination with the rich set of fast ion diagnostics available on the MAST Upgrade, for a more constrained modeling of the fast ion dynamics in fusion reactor relevant scenarios.